Intermetallic Nanocrystals: Seed‐Mediated Synthesis and Applications in Electrocatalytic Reduction Reactions. Issue 69 (7th October 2022) - Guo, Jingchun; Jiao, Shilong; Ya, Xiuying; Zheng, Huiling; Wang, Ran; Yu, Jiao; Wang, Huanyu; Zhang, Zhilin; Liu, Wei; He, Congxiao; Fu, Xucheng
Abstract: In recent years, intermetallic nanocrystals (IMNCs) have attracted extensive attention in the field of electrocatalysis. However, precise control over the size, shape, composition, structure, and exposed crystal facet of IMNCs seems to be a challenge to the traditional method of high‐temperature annealing although these parameters have a significant effect on the electrocatalytic performance. Controllable synthesis of IMNCs by the wet chemistry method in the liquid phase shows great potential compared with the traditional high‐temperature annealing method. In this Review, we attempt to summarize the preparation of IMNCs by the seed‐mediated synthesis in the liquid phase, as well as their applications in electrocatalytic reduction reactions. Several representative examples are purposely selected for highlighting the huge potential of the seed‐mediated synthesis approach in chemical synthesis. Specifically, we personally perceive the seed‐mediated synthesis approach as a promising tool in the future for precise control over the size, shape, composition, structure, and exposed crystal facet of IMNCs. Abstract : Intermetallic nanocrystals (IMNCs) have attracted extensive attention as electrocatalysis. However, precise control over the size, shape, composition, structure, and exposed crystal facet of IMNCs seems to be a challenge, although these parameters have a significant effect on the electrocatalytic performance. The seed‐mediated synthesis approach is a promising tool for precise control over these parameters of IMNCs.